Addressing Public Speaking Anxiety in Multicultural Counselling: The Use of Cognitive-Behavioural Therapy for International Students - Anwar, Moh. Khoerul; Haq, Muhammad Izzul; Salma, Diafi; Wang, Zhongjun (Jurnal Kajian Bimbingan dan Konseling, 2022)
Several studies have highlighted the importance of Cognitive Behavioural Therapy (CBT) in reducing public speaking anxiety. The studies also denote the increase of confidence by strengthening self-efficacy. This study explores previous studies that uncover the use of CBT in dealing with public anxiety to identify its potential as part of multicultural counseling for international students in higher education. International students have different academic and learning cultures, as well as social environments, affecting the development of certain anxiety in dealing with pressures to adapt to new environments. Therefore, it positions the investigation of CBT’s ability to reduce public speaking anxiety for international students as highly essential. This study contends that CBT is a useful technique to unpack irrational fear of speaking in public and promote self-efficacy, developing confidence and leading to good mental health. However, given the nature of targeted intervention are international students, multicultural counseling competencies are undoubtedly required for the therapy.